PERANCANGAN KAWASAN AGROWISATA BERBASIS HORTIKULTURA DI KECAMATAN PONTIANAK UTARA - Calvin, John; affrilyno, affrilyno; Purnomo, Yudi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
North Pontianak District is a region in the Equator City that serves as a significant agricultural production area, with a primary focus on horticultural commodities, particularly vegetables. However, this potential has not yet been optimally utilized in efforts to empower the area and its local communities. There is a pressing need for a relevant land-use function to enhance the development of local agricultural products. The objective of designing a Horticulture-Based Agri-tourism Area in North Pontianak District is to serve as a strategic approach for empowering the area by establishing it as a center for agricultural business and managing horticultural land potential, thus contributing to the development of agricultural tourism destinations. In addition to food production, agricultural land can be integrated into a recreational and educational space to attract tourist visits. The design method applied is the five-step design process according to Snyder Catanese, which includes initiation, preparation, proposal submission, action, and evaluation. The outcome of this design is the creation of an agri-tourism area that integrates agricultural, recreational, and educational elements, focusing on the empowerment of local communities and the optimization of agricultural land potential.